Environmental invariants, their statistical evaluation and use - Semkin, B. I.; Varchenko L. I., L. I. (Проблемы ботаники Южной Сибири и Монголии, 2019)
The ecological invariants of communities and the influence of natural and anthropogenic environmental factors on them are considered.